Effects of exogenous sex hormones on mouse estrous cycle, vaginal microbiota and immune cells - de Gregorio, Priscilla Romina (2018)
Sex hormones are oft en administered to mice in vaginal microbial studies in order to synchronize estrous. Our objective was to evaluate the effect of estradiol-hemi succinate (EH) or medroxyprogest erone-acetate (MPA) administration on estrous cycle, vaginal microbiota, and immune cell populations of various organs in a murine model. Two-month-old female BALB/cmice were intramuscularly injected with EH (day -2) or MPA (day -5) to induce estrous (E) or diestrous (DE), respectively. On sampling days (Sd) 0, 2, 6 and 8, vaginal washings (v.w.), vagina, blood, spleen and bone marrow (BM) samples were taken. Most of the animals remained in E or DE states until Sd 6 after EH or MPA administration, respectively. The numberof cultivable vaginal bacteria was not modified by hormonal treatments; higher quantities weredetected in mice in E. Only EH administration modifi ed serum sex hormone levels, increasing serum estradiol on Sd 0. In v.w., myeloid population was dominant while lymphoid populations were not detected. Only MPA administration induced a reduction in myeloid cells on Sd 0.Hormonal treatments did not aff ect myeloid populations in BM but caused a slight decrease in T and B cells. In spleen, hormonal administration did not aff ect B or T population size while an increase in mature B cells and a decrease in immature B cells were observed in MPA-treated mice compared with EH-treated mice. Th us, although both hormonal treatments induced slight changes in some of the parameters evaluated compared to control animals, adequately standardized and consistent experimental protocols were established for further studies.